Melatonin Treatment Inhibits the Growth of Xanthomonas oryzae pv. oryzae - Chen, Xian; Sun, Cheng; Laborda, Pedro; Zhao, Yancun; Palmer, Ian; Fu, Zheng Qing; Qiu, Jingping; Liu, Fengquan (Frontiers in Microbiology, 2018)
Xanthomonas oryzae pv. oryzae (Xoo) causes rice bacterial blight, one of the most widespread and destructive diseases in rice-growing regions worldwide. Melatonin enhances pathogen resistance by inducing the plant innate immunity, but the direct effect of melatonin on plant pathogenic bacteria is poorly understood. In this study, we investigated the direct effects of melatonin on Xoo. Exogenous melatonin at 200 μg/mL significantly inhibited the proliferation of Xoo and reduced the mRNA expression of 5 cell-division genes. Melatonin at 200 μg/mL also inhibited the motility and biofilm formation of Xoo. Notably, melatonin changed the cell structure of Xoo length. To provide deeper insight into the mechanisms underlying this antibacterial activity, we examined global gene expression changes in PXO99 in response to the application of 200 μg/mL melatonin using RNA sequencing (RNA-seq). A wide range of DEGs related to catalytic activity and metal-binding activity were down-regulated under melatonin treatment. The DEGs responsible for carbohydrate metabolism and amino acid metabolism were also down-regulated. These results suggest that the inhibitory mechanism of melatonin on Xoo proliferation may involve regulation of cell division, along with reducing the concentration or activity of enzymes involved in metabolism.